2011
DOI: 10.1186/1742-2094-8-149
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the KATP channel opener diazoxide ameliorates disease progression in a murine model of multiple sclerosis

Abstract: BackgroundMultiple Sclerosis (MS) is an acquired inflammatory demyelinating disorder of the central nervous system (CNS) and is the leading cause of nontraumatic disability among young adults. Activated microglial cells are important effectors of demyelination and neurodegeneration, by secreting cytokines and others neurotoxic agents. Previous studies have demonstrated that microglia expresses ATP-sensitive potassium (KATP) channels and its pharmacological activation can provide neuroprotective and anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
61
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 61 publications
(64 reference statements)
5
61
0
Order By: Relevance
“…Recently, we and others have reported novel roles for Dzx as an anti-inflammatory agent, which could contribute to the neuroprotective effects. Dzx has been shown to prevent microglial TNF , NO and interleukin-6 production after activation with different stimuli in vitro (Zhou et al, 2008;Virgili et al, 2011). Here, our in vivo results demonstrated that Dzx preserves neurons and decreases microglial reaction against an excitotoxic neurodegenerative insult, possibly through its anti-inflammatory action.…”
Section: Diazoxide Enhances the Nmda-induced Presence Of Sp8-gfap-possupporting
confidence: 57%
See 4 more Smart Citations
“…Recently, we and others have reported novel roles for Dzx as an anti-inflammatory agent, which could contribute to the neuroprotective effects. Dzx has been shown to prevent microglial TNF , NO and interleukin-6 production after activation with different stimuli in vitro (Zhou et al, 2008;Virgili et al, 2011). Here, our in vivo results demonstrated that Dzx preserves neurons and decreases microglial reaction against an excitotoxic neurodegenerative insult, possibly through its anti-inflammatory action.…”
Section: Diazoxide Enhances the Nmda-induced Presence Of Sp8-gfap-possupporting
confidence: 57%
“…Other studies in different animal models have shown that Dzx protects against cell death from excitotoxicity or inflammation, generating beneficial outcomes (Zhou et al, 2008;Liu et al, 2010;Virgili et al, 2011) and modulating the innate immune response (Virgili et al, 2014).…”
Section: Diazoxide Enhances the Nmda-induced Presence Of Sp8-gfap-posmentioning
confidence: 99%
See 3 more Smart Citations